Pengaruh Personal Selling Agen Dan Kualitas Produk Terhadap Keputusan Pembelian Nasabah Pada PT.Sun Life Financial Cabang Medan - Maisyaroh, Elvira; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
The insurance business is growing in Indonesia, causing fierce competition. Consumer behavior in the purchase process begins with the purchase interest where consumers get information, references and even compare one product with another before making a purchase. This study aims to examine empirically the influence of (1) personal sellingagen and product quality on purchasing decisions, (2) personal selling on purchasing decisions, (3) product quality on purchasing decisions. The research design used is causal quantitative research design. The method of data collection using questionnaires, which were then analyzed using multiple regression with classical assumption test. The sample in this study are customers of PT.Sun Life Financial Medan branch that purchased at least two different and similar programs involving 94 respondents. The results showed that there is a simultaneous relationship of personal selling and product quality to the purchase decision of 0.785; there is a partial significant effect of personal selling on the purchase decision of 0.445; and there is a partial significant effect of product quality on the purchase decision of 0.173. Thus it can be concluded that the existence of a good personal selling process and product quality in accordance with customer needs will affect the customer's decision in choosing insurance.